2023
DOI: 10.1021/acsnano.2c08635
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Perturbative, Low-Noise Surface Coating for Sensitive Force-Gradient Detection of Electron Spin Resonance in Thin Films

Abstract: The sensitivity of magnetic resonance force microscopy (MRFM) is limited by surface noise. Coating a thin-film polymer sample with metal has been shown to decrease, by orders of magnitude, sample-related force noise and frequency noise in MRFM experiments. Using both MRFM and inductively detected measurements of electron-spin resonance, we show that thermally evaporating a 12 nm gold layer on a 40 nm nitroxide-doped polystyrene film inactivates the nitroxide spin labels to a depth of 20 nm, making single-spin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…The optimization of the µ parameter demands the use of small magnetic particles to induce large magnetic gradients [ 257 ] and to minimize as possible the sources of cantilever friction and the scanning temperature [ 258 ]. Additionally, it was recently reported that the sample coating with few nanometers of a thin metal like gold can significantly reduce the signal-to-noise ratio up to 20-fold [ 259 ], and the sensitivity of MRFM can be improved up to 10 µ when the RF coil is replaced by a microwave micro-strip resonator [ 260 ]. Finally, MRFM can monitor statistical spin fluctuations rendering larger polarizations, which have narrower distributions compared to thermal polarizations [ 261 ].…”
Section: Mfm Operational Modesmentioning
confidence: 99%
“…The optimization of the µ parameter demands the use of small magnetic particles to induce large magnetic gradients [ 257 ] and to minimize as possible the sources of cantilever friction and the scanning temperature [ 258 ]. Additionally, it was recently reported that the sample coating with few nanometers of a thin metal like gold can significantly reduce the signal-to-noise ratio up to 20-fold [ 259 ], and the sensitivity of MRFM can be improved up to 10 µ when the RF coil is replaced by a microwave micro-strip resonator [ 260 ]. Finally, MRFM can monitor statistical spin fluctuations rendering larger polarizations, which have narrower distributions compared to thermal polarizations [ 261 ].…”
Section: Mfm Operational Modesmentioning
confidence: 99%